Inflammatory stimuli promote growth and invasion of pancreatic cancer cells through NF-κB pathway dependent repression of PP2Ac. Issue 3 (1st February 2016) - Tao, Min; Liu, Lu; Shen, Meng; Zhi, Qiaoming; Gong, Fei-Ran; Zhou, Binhua P.; Wu, Yadi; Liu, Haiyan; Chen, Kai; Shen, Bairong; Wu, Meng-Yao; Shou, Liu-Mei; et al.
ABSTRACT: Previous studies have indicated that inflammatory stimulation represses protein phosphatase 2A (PP2A), a well-known tumor suppressor. However, whether PP2A repression participates in pancreatic cancer progression has not been verified. We used lipopolysaccharide (LPS) and macrophage-conditioned medium (MCM) to establish in vitro inflammation models, and investigated whether inflammatory stimuli affect pancreatic cancer cell growth and invasion PP2A catalytic subunit (PP2Ac)-dependently. Via nude mouse models of orthotopic tumor xenografts and dibutyltin dichloride (DBTC)-induced chronic pancreatitis, we evaluated the effect of an inflammatory microenvironment on PP2Ac expression in vivo . We cloned the PP2Acα and PP2Acβ isoform promoters to investigate the PP2Ac transcriptional regulation mechanisms. MCM accelerated pancreatic cancer cell growth; MCM and LPS promoted cell invasion. DBTC promoted xenograft growth and metastasis, induced tumor-associated macrophage infiltration, promoted angiogenesis, activated the nuclear factor-κB (NF-κB) pathway, and repressed PP2Ac expression. In vitro, LPS and MCM downregulated PP2Ac mRNA and protein. PP2Acα overexpression attenuated JNK, ERK, PKC, and IKK phosphorylation, and impaired LPS/MCM-stimulated cell invasion and MCM-promoted cell growth. LPS and MCM activated the NF-κB pathway in vitro . LPS and MCM induced IKK and IκB phosphorylation, leading to p65/RelA nuclear translocation and transcriptional activation. Overexpression of the dominant negative forms of IKKα attenuated LPS and MCM downregulation of PP2Ac, suggesting inflammatory stimuli repress PP2Ac expression NF-κB pathway–dependently. Luciferase reporter gene assay verified that LPS and MCM downregulated PP2Ac transcription through an NF-κB–dependent pathway. Our study presents a new mechanism in inflammation-driven cancer progression through NF-κB pathway–dependent PP2Ac repression.